A trace ruthenium modified cobalt-based nanocage catalyst and preparation and application thereof

CN120250065BActive Publication Date: 2026-10-09ZHEJIANG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510340791.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-03-21
Publication Date
2026-10-09
Estimated Expiration
2045-03-21

AI Technical Summary

Technical Problem

然而现有电化学乙烯氧化生成2-溴乙醇体系面临三大瓶颈:(1)传质限制,乙烯在水性电解质中溶解度低(35g/L),高电流密度下法拉第效率急剧下降;(2)过度氧化,高阳极电位会引发乙烯过度氧化生成CO2等副产品

Benefits of technology

[0024] (1) A trace ruthenium-modified cobalt tetroxide nanocage catalyst was prepared by a simple ion adsorption method. The preparation method is simple, reproducible, and suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120250065B_ABST
    Figure CN120250065B_ABST
Patent Text Reader

Abstract

The application discloses a method for synthesizing trace ruthenium modified cobalt tetraoxide nanocage catalyst by ion exchange method, and comprises the following steps: dropping dimethyl imidazole methanol solution into a methanol solution containing cobalt nitrate hexahydrate to obtain a precursor ZIF67 through reaction; dropping a ruthenium chloride ethanol solution into an ethanol solution containing the ZIF67 to obtain a ruthenium modified ZIF67; and calcining the ruthenium modified ZIF67 to obtain the trace ruthenium modified cobalt tetraoxide nanocage catalyst. The application also discloses application of the catalyst in electrocatalytic oxidation of ethylene to prepare 2-bromoethanol, and the catalyst shows high intrinsic activity and high catalytic activity. In the application, trace metal ruthenium is introduced into the cobalt-based catalyst to form rich Ru-O-Co asymmetric active sites, and the electronic structure of the catalyst surface and the activation energy barrier of bromide ions in the electrocatalytic reaction process are changed by hetero-metal doping, so that the catalytic performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalytic material preparation technology, specifically to a trace ruthenium-modified cobalt tetroxide nanocatalyst and its preparation and application. Background Technology

[0002] 2-Bromoethanol is an organic compound of great importance in organic synthesis. It can be used to synthesize various important organic compounds, such as ethylene glycol, diethylene glycol, and haloethers, through substitution, elimination, and oxidation reactions. These compounds are widely used in chemical production, for example, in the manufacture of polyester fibers, plastics, and solvents. 2-Bromoethanol is also a crucial raw material for the synthesis of many drugs, including antiviral and antitumor drugs, making it significant for pharmaceutical research and development.

[0003] In recent years, the electrochemical oxidation of ethylene (EOR) to produce high-value chemicals has attracted increasing attention. Compared with the traditional chemical method of direct oxidation of hypochlorous acid, the one-step electrocatalytic synthesis of high-value-added 2-bromoethanol provides an environmentally friendly, sustainable, and low-cost route. Compared with the traditional chemical method, it has advantages such as low transportation and processing costs and less pollution. Among the various pathways of ethylene electrocatalytic oxidation, the electrochemical oxidation of ethylene to 2-bromoethanol has the following advantages: (1) The bromine evolution potential (BrER) is low, so from a thermodynamic point of view, BrER is more efficient at low battery voltages. (2) Br2 is moderately soluble in water (34 g / L at room temperature). Br2 reactants are still readily available in the aqueous phase to promote the reaction of ethylene to 2-bromoethanol. (3) All bromine derivatives (including 2-bromoethanol, bromoethane, etc.) and bromine itself are moderately to highly soluble in aqueous electrolytes. If the oxygen evolution reaction does not occur at the anode, the reactant ethylene can be over-fed in the recycling loop without any downstream purification steps, thereby inhibiting the formation of 1,2-dibromoethane (Br2Et) byproducts. However, existing electrochemical systems for the oxidation of ethylene to 2-bromoethanol face three major bottlenecks: (1) mass transfer limitations, as ethylene has low solubility in aqueous electrolytes (35 g / L), and the Faraday efficiency drops sharply at high current densities; (2) over-oxidation, as high anodic potentials can lead to over-oxidation of ethylene to produce byproducts such as CO2. Therefore, systems requiring low current densities (<100 mA / cm²) are necessary. 2 (2) Low current density is used to maintain high selectivity and high Faraday efficiency to the maximum extent, but the low current density leads to a surge in the demand for electrolyzer area, which significantly increases the cost of industrialization. (3) Cost constraints: The high cost of currently high-performance noble metal catalysts (e.g., size-stable anodes with high Ru and / or Ir content (~30%)) makes their industrial application a challenge. Therefore, the development of efficient, low-cost and highly stable catalysts remains a key problem to be solved.

[0004] Co3O4 is a typical AB2O4-type spinel oxide, attracting considerable attention due to its low cost, high elemental abundance, and controlled geometric Co sites. However, for the electrocatalytic oxidation of ethylene to 2-bromoethanol, Co3O4 still faces limitations due to its slow kinetics and stability. Recent studies have shown that highly dispersed single-atom catalysts are beneficial for improving the activity of electrocatalytic ethylene oxidation to 2-bromoethanol while reducing the use of noble metals Ru, Ir, and Pt. Currently, there are many methods for synthesizing noble metal-supported cobalt tetroxide-based catalysts. For example, Chinese patent document CN118976514A describes a method for preparing a Pt single-atom and nanoparticle coexisting catalyst. This method first mixes ZIF-67 with water to obtain a suspension; then mixes a platinum source with the suspension to obtain a platinum aqueous solution; finally, the platinum aqueous solution is heated, rotary evaporated, first dried, and calcined to obtain the Pt single-atom and nanoparticle coexisting catalyst. This method achieves dual activation of lattice oxygen and molecular oxygen, further improving catalytic efficiency. However, the preparation process is relatively complex, and the optimal noble metal loading is 4-6 wt%, resulting in high catalyst cost. Therefore, a simpler and more effective method is needed that is cost-effective while ensuring the improvement of the intrinsic performance and electrocatalytic activity of the catalyst. Summary of the Invention

[0005] Based on the problems in the prior art, this invention studies the preparation of a trace ruthenium-modified cobalt tetroxide nanocage catalyst by a simple ion adsorption method. By introducing trace amounts of metallic ruthenium into the cobalt-based catalyst, Ru-O-Co asymmetric bimetallic sites are formed. At the same time, the electronic structure of the catalyst surface and the activation energy barrier of bromide ions in the electrocatalytic oxidation of ethylene to 2-bromoethanol are changed by heterometallic doping, thereby improving the catalytic performance of electrocatalytic oxidation of ethylene to 2-bromoethanol.

[0006] To achieve the above-mentioned objectives, the present invention employs the following technical solution.

[0007] This invention first provides a method for preparing a trace ruthenium-modified cobalt-based nanocage catalyst. This method can prepare a cobalt tetroxide nanocage catalyst by a simple ion adsorption method, and introduce trace amounts of ruthenium into cobalt tetroxide to modify it, thereby obtaining a trace ruthenium-modified cobalt tetroxide nanocage catalyst with high electrocatalytic activity for the oxidation of ethylene to 2-bromoethanol.

[0008] A method for preparing a trace ruthenium-modified cobalt tetroxide nanocage catalyst includes:

[0009] (1) Cobalt nitrate hexahydrate and dimethylimidazole were added to methanol and stirred until completely dissolved to obtain methanol solutions of cobalt nitrate hexahydrate and dimethylimidazole, respectively.

[0010] (2) The above dimethylimidazole methanol solution was added dropwise to the cobalt nitrate hexahydrate methanol solution and stirred at room temperature to obtain a turbid purple solution.

[0011] (3) The product obtained in step (2) was washed sequentially with methanol and anhydrous ethanol, filtered, dried in a vacuum oven, and ground to obtain the precursor ZIF67.

[0012] (4) Add ZIF67 and ruthenium chloride to ethanol respectively, and stir continuously until they are evenly dispersed to obtain ethanol solutions of ruthenium chloride and ethanol solutions containing ZIF67 respectively.

[0013] (5) Add the ruthenium chloride ethanol solution dropwise to the ethanol solution containing ZIF67, stir thoroughly to allow the ruthenium ions in the solution to be fully adsorbed on the surface of ZIF67, then wash with anhydrous ethanol, filter, dry in a vacuum oven, remove and grind to obtain trace ruthenium-modified ZIF67. At this point, ruthenium ions are adsorbed on the surface of ZIF67 to form trace ruthenium-modified ZIF67.

[0014] (6) The trace ruthenium-modified ZIF67 is calcined in a muffle furnace to obtain the trace ruthenium-modified cobalt tetroxide nanocage catalyst. During the high-temperature calcination process, ZIF67 forms a hollow polyhedral shape composed of cobalt tetroxide nanoparticles, namely cobalt tetroxide nanocages. At the same time, the ruthenium ions originally adsorbed on the surface of ZIF67 are oxidized into ruthenium oxide nanoparticles during the calcination process and loaded onto the surface of the cobalt tetroxide nanocages.

[0015] This invention introduces ruthenium metal into a cobalt-based catalyst through a simple ion adsorption method to form Ru-O-Co asymmetric bimetallic sites. At the same time, the heterometal doping changes the electronic structure of the catalyst surface and the activation energy barrier of bromide ions in the electrocatalytic oxidation of ethylene to 2-bromoethanol, thereby improving the catalytic performance of the electrocatalytic oxidation of ethylene to 2-bromoethanol.

[0016] In step (1), the molar ratio of cobalt nitrate hexahydrate to dimethylimidazole is 1:2 to 1:4. This optimal molar ratio of cobalt nitrate hexahydrate to dimethylimidazole ensures sufficient coordination between the two, allowing for nucleation growth to obtain the precursor ZIF67. The total volume of methanol used in the methanol solutions of cobalt nitrate hexahydrate and dimethylimidazole formed in step (1) satisfies a ratio of 40–120 mL to 3–9 mmol relative to the molar amount of cobalt nitrate hexahydrate added in step (1). Under these conditions, the ZIF67 prepared is a regular polyhedron, which is beneficial for the subsequent formation of a hollow cage-like framework.

[0017] In steps (4) to (5), the mass of ruthenium chloride added is 4 to 16 wt% of the mass of ZIF67 added. Here, the mass of ruthenium added is limited to a suitable range. In the trace ruthenium-modified cobalt tetroxide nanocage catalyst, if the doping amount of ruthenium is too low, the change of the electronic structure of the catalyst surface by ruthenium is not obvious, and sufficient Ru-O-Co asymmetric sites cannot be formed, thus affecting the catalytic activity and selectivity; if the doping amount of ruthenium is too high, it may cause the ruthenium oxide particles adsorbed on the surface of the cobalt tetroxide nanocage to agglomerate and become deactivated.

[0018] In step (6), to ensure the complete oxidation of the catalyst precursor, calcination was carried out in a muffle furnace at 300-400℃ for 1-2 hours. The resulting trace ruthenium-modified cobalt tetroxide nanocage catalyst not only maintained good oxygen evolution suppression performance but also further improved the catalytic activity and selectivity of the main product 2-bromoethanol.

[0019] This invention also provides a trace ruthenium-modified cobalt tetroxide nanocage catalyst prepared by the above method, wherein the trace ruthenium-modified cobalt tetroxide nanocage catalyst is composed of cobalt tetroxide and trace amounts of ruthenium oxide. The microstructure of the trace ruthenium-modified cobalt tetroxide nanocage catalyst is as follows: several cobalt tetroxide nanoparticles form a framework, enclosing several hollow polyhedra, i.e., cobalt tetroxide nanocages; ruthenium oxide nanoparticles are adsorbed on the surface of the cobalt tetroxide nanocages. The ruthenium loading is 0.22-0.56 wt%, where ruthenium loading refers to the mass percentage of ruthenium in the catalyst.

[0020] The present invention also provides the application of the above-mentioned trace ruthenium-modified cobalt tetroxide nanocage catalyst in the electrocatalytic preparation of 2-bromoethanol from ethylene, as detailed below.

[0021] The trace ruthenium-modified cobalt tetroxide nanocage catalyst of this invention was attached to carbon paper as a working electrode, with a loading of 0.25-1.0 mg / cm³. -2 An electrocatalytic reaction to produce 2-bromoethanol from ethylene was carried out in an H-type electrolytic cell using a 0.1 mol / L potassium bromide solution as the electrolyte, an ethylene blowing rate of 15 mL / min, an Ag / AgCl reference electrode, and a platinum sheet as the counter electrode.

[0022] This invention prepares a trace ruthenium-modified cobalt tetroxide nanocage catalyst using a simple ion adsorption method. By introducing metallic ruthenium into a cobalt-based catalyst and modifying its surface, a trace ruthenium-modified cobalt tetroxide nanocage catalyst is formed. The ruthenium doping alters the electronic structure of the catalytic material and lowers the activation barrier of bromide ions during the electrocatalytic production of 2-bromoethanol from ethylene. Simultaneously, it forms abundant Ru-O-Co asymmetric sites, thereby improving the catalytic activity and selectivity of the electrocatalytic production of 2-bromoethanol from ethylene.

[0023] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0024] (1) A trace ruthenium-modified cobalt tetroxide nanocage catalyst was prepared by a simple ion adsorption method. The preparation method is simple, reproducible, and suitable for industrial production.

[0025] (2) The present invention prepares a trace ruthenium-modified cobalt tetroxide nanocage catalyst by a simple ion adsorption method, wherein the Ru loading is 0.22-0.56 wt%, the noble metal loading is small, and it has a cost advantage compared with other noble metal catalysts.

[0026] (3) The trace ruthenium-modified cobalt tetroxide nanocage catalyst prepared by the present invention has a hollow nanocage structure that improves the conductivity and intrinsic electrocatalytic performance of the catalyst. For example, the catalyst has a large current density and a low overpotential in the test potential range, showing excellent electrocatalytic potential.

[0027] (4) The trace ruthenium-modified cobalt tetroxide nanocage catalyst prepared in this invention successfully introduces metallic ruthenium into the cobalt-based catalyst, forming abundant Ru-O-Co asymmetric active sites. This alters the catalyst's electronic structure, such as electron cloud density, and the activation energy of bromide ions during the electrocatalytic oxidation of ethylene to 2-bromoethanol, thereby improving the catalytic performance of ethylene oxidation to 2-bromoethanol. For example, at 1.4V vs. RHE, compared to the unmodified cobalt tetroxide nanocage catalyst, its 2-bromoethanol Faraday efficiency increased from 84.4% to 93.9%.

[0028] (5) This invention uses clean and renewable electrical energy to achieve the efficient preparation of 2-bromoethanol, an important chemical and pharmaceutical intermediate, which is in line with the concept of green, environmentally friendly and sustainable development. Attached Figure Description

[0029] Figure 1 This is a SEM image of the trace ruthenium-modified cobalt tetroxide nanocage catalyst prepared in Example 1 of this invention before calcination.

[0030] Figure 2 This is a TEM image of the trace ruthenium-modified cobalt tetroxide nanocage catalyst prepared in Example 1 of the present invention.

[0031] Figure 3 The image shows the XRD pattern of the catalyst prepared in Example 1 of this invention.

[0032] Figure 4 The above are electrochemical polarization curves of the catalysts prepared in Example 1, Comparative Examples 1 and 2 of this invention in a three-electrode reaction cell and 0.1M potassium bromide electrolyte.

[0033] Figure 5 The Tafel slope diagrams are shown for the catalysts prepared in Example 1, Comparative Examples 1 and 2 of this invention in a three-electrode reaction cell and 0.1M potassium bromide electrolyte.

[0034] Figure 6 The image shows the 2-bromoethanol Faraday efficiency of the catalysts prepared in Example 1, Comparative Examples 1 and 2 of this invention in a three-electrode reaction cell and 0.1M potassium bromide electrolyte. Detailed Implementation

[0035] The present invention will be further described below with reference to the accompanying drawings and specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Experimental methods in the following embodiments, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer.

[0036] Example 1

[0037] Preparation steps of a trace ruthenium-modified cobalt tetroxide nanocage catalyst:

[0038] Step 1: Weigh 0.873g (about 3mmol) of cobalt nitrate hexahydrate and 0.984g of dimethylimidazole on an electronic balance. The molar ratio of cobalt nitrate to dimethylimidazole is 1:4. Dissolve them completely in 30ml and 10ml of methanol respectively under magnetic stirring.

[0039] Step 2: Slowly add the prepared dimethylimidazole methanol solution dropwise to the cobalt nitrate hexahydrate methanol solution, and react fully for 24 hours under magnetic stirring at 600 rpm to obtain a turbid purple solution product.

[0040] Step 3: Wash the product from Step 2 sequentially with methanol and anhydrous ethanol, filter, dry in a vacuum oven at 60℃ for 12 hours, and then grind to obtain product ZIF67.

[0041] Step 4: Weigh 100 mg of ZIF67 from Step 3 using an electronic balance and disperse it thoroughly in 75 ml of ethanol with magnetic stirring. Weigh 8 mg of ruthenium chloride using an electronic balance and dissolve it thoroughly in 5 ml of ethanol with magnetic stirring.

[0042] Step 5: Slowly add the prepared ruthenium chloride ethanol solution dropwise to the ZIF67 ethanol solution, and react fully for 2 hours under magnetic stirring at 600 rpm.

[0043] Step 6: Wash the product from Step 2 with anhydrous ethanol, filter it, dry it in a vacuum oven at 60°C for 12 hours, take it out and grind it to obtain ruthenium ion-supported ZIF67, i.e., trace ruthenium-modified ZIF67.

[0044] Step 6: The product from Step 6 is calcined in a muffle furnace at 300°C for 2 hours to finally obtain a trace amount of ruthenium-modified cobalt tetroxide nanocage catalyst.

[0045] Example 2

[0046] Preparation steps of a trace ruthenium-modified cobalt tetroxide nanocage catalyst:

[0047] Step 1: Weigh 1.746g (about 6mmol) of cobalt nitrate hexahydrate and 1.968g of dimethylimidazole on an electronic balance, i.e., the molar ratio of cobalt nitrate to dimethylimidazole is 1:4. Dissolve them completely in 60ml and 20ml of methanol respectively under magnetic stirring.

[0048] Step 2: Slowly add the prepared dimethylimidazole methanol solution dropwise to the cobalt nitrate hexahydrate methanol solution, and react fully for 24 hours under magnetic stirring at 600 rpm to obtain a turbid purple solution.

[0049] Step 3: Wash the product from Step 2 with methanol and anhydrous ethanol, filter it, dry it in a vacuum oven at 60°C for 12 hours, take it out and grind it to obtain product ZIF67.

[0050] Step 4: Weigh 100 mg of ZIF67 obtained in Step 3 using an electronic balance, and disperse it thoroughly in 75 ml of ethanol under magnetic stirring. Weigh 4 mg of ruthenium chloride using an electronic balance, and dissolve it thoroughly in 5 ml of ethanol under magnetic stirring.

[0051] Step 5: Slowly add the prepared ruthenium chloride ethanol solution dropwise to the ZIF67 ethanol solution, and react fully for 2 hours under magnetic stirring at 600 rpm.

[0052] Step 6: Wash the product from Step 2 with anhydrous ethanol, filter it, dry it in a vacuum oven at 60°C for 12 hours, take it out and grind it to obtain trace ruthenium-modified ZIF67.

[0053] Step 6: The product from Step 6 is calcined in a muffle furnace at 350°C for 2 hours to finally obtain a trace amount of ruthenium-modified cobalt tetroxide nanocage catalyst.

[0054] Example 3

[0055] Preparation steps of a trace ruthenium-modified cobalt tetroxide nanocage catalyst:

[0056] Step 1: Weigh 2.619g (about 9mmol) of cobalt nitrate hexahydrate and 2.952g of dimethylimidazole on an electronic balance. The molar ratio of cobalt nitrate to dimethylimidazole is 1:4. Dissolve them completely in 90ml and 30ml of methanol respectively under magnetic stirring.

[0057] Step 2: Slowly add the prepared dimethylimidazole methanol solution dropwise to the cobalt nitrate hexahydrate methanol solution, and react fully for 24 hours under magnetic stirring at 600 rpm to obtain a turbid purple solution product.

[0058] Step 3: Wash the product from Step 2 with methanol and anhydrous ethanol, filter it, dry it in a vacuum oven at 60°C for 12 hours, and then grind it to obtain product ZIF67.

[0059] Step 4: Weigh 50 mg of ZIF67 from Step 3 using an electronic balance and disperse it thoroughly in 38 ml of ethanol with magnetic stirring. Weigh 8 mg of ruthenium chloride using an electronic balance and dissolve it thoroughly in 2 ml of ethanol with magnetic stirring.

[0060] Step 5: Slowly add the prepared ruthenium chloride ethanol solution dropwise to the ZIF67 ethanol solution, and react fully for 2 hours under magnetic stirring at 600 rpm.

[0061] Step 6: Wash the product from Step 2 with anhydrous ethanol, filter it, dry it in a vacuum oven at 60°C for 12 hours, take it out and grind it to obtain trace ruthenium-modified ZIF67.

[0062] Step 6: The product from Step 6 is calcined in a muffle furnace at 400°C for 2 hours to finally obtain a trace amount of ruthenium-modified cobalt tetroxide nanocage catalyst.

[0063] Example 4

[0064] Compared to Example 1, this example adjusts the molar ratio of cobalt nitrate hexahydrate and dimethylimidazole in step one to 1:2, while the rest remains the same.

[0065] Example 5

[0066] Compared to Example 1, this example adjusts the molar ratio of cobalt nitrate hexahydrate and dimethylimidazole in step one to 1:3, while the rest remains the same.

[0067] Example 6

[0068] Compared to Example 1, this example adjusts the calcination time in step six to 1 hour. The rest is the same as in Example 1.

[0069] Example 7

[0070] Compared to Example 1, step one of this example is as follows: 0.873 g (approximately 3 mmol) of cobalt nitrate hexahydrate and 0.984 g of dimethylimidazole are weighed using an electronic balance, i.e., the molar ratio of cobalt nitrate to dimethylimidazole is 1:4. The mixture is then fully dissolved in 90 ml and 30 ml of methanol, respectively, under magnetic stirring. The rest is the same as in Example 1.

[0071] Example 8

[0072] Compared to Example 1, step one of this example is as follows: 2.619 g (approximately 9 mmol) of cobalt nitrate hexahydrate and 2.952 g of dimethylimidazole are weighed using an electronic balance, i.e., the molar ratio of cobalt nitrate to dimethylimidazole is 1:4. These are then fully dissolved in 30 ml and 10 ml of methanol, respectively, under magnetic stirring. The rest is the same as in Example 1.

[0073] SEM and TEM analyses revealed that the trace ruthenium-modified cobalt tetroxide nanocage catalysts prepared in each embodiment exhibited a hollow cage-like structure composed of several cobalt tetroxide nanoparticles, with ruthenium oxide nanoparticles supported on the surface of the cage-like structure. The cobalt tetroxide nanoparticles enclosed several hollow polyhedra, forming the cobalt tetroxide nanocages, with ruthenium oxide nanoparticles supported on the surface of the cobalt tetroxide nanocages. Figure 1 and Figure 2 ,in Figure 1 The image shows the SEM image of the trace ruthenium-modified cobalt tetroxide nanocage catalyst prepared in Example 1 before calcination, which is the SEM image of the catalyst precursor obtained at the end of step five in Example 1, namely the trace ruthenium-modified ZIF67.

[0074] Figure 2 TEM image of the trace ruthenium-modified cobalt tetroxide nanocage catalyst prepared in Example 1. From... Figure 1 It can be seen that the trace ruthenium-modified ZIF67 before calcination is a regular polyhedron with several nanoparticles loaded on its outer surface. These nanoparticles are adsorbed ruthenium ions. Further analysis reveals... Figure 2 It can be seen that after calcination, ZIF67 is transformed into cobalt tetroxide nanoparticles, inheriting the regular polyhedral morphology of the original ZIF67. After calcination, the regular polyhedrons of ZIF67 form hollow polyhedra with cobalt tetroxide nanoparticles as the framework, namely cobalt tetroxide nanocages. The ruthenium ions originally adsorbed on the surface of ZIF67 are oxidized into ruthenium oxide nanoparticles after calcination and loaded on the cage-like structure surface surrounded by cobalt tetroxide nanoparticles.

[0075] XRD analysis confirmed that the main phase of the trace ruthenium-modified cobalt tetroxide nanocage catalysts prepared in each embodiment was Co3O4, with the Co(311) crystal plane being the most exposed. Trace Ru was not observed in the XRD, but its content was determined by precise ICP-OES analysis to be 0.22-0.56 wt% in the catalyst. For example, Figure 3 The XRD pattern of the trace ruthenium-modified cobalt tetroxide nanocage catalyst prepared in Example 1 is shown in the figure. It can be seen from the figure that the main component of the trace ruthenium-modified cobalt tetroxide nanocage catalyst prepared in Example 1 is Co3O4. Due to its ultra-low loading in the catalyst, the presence of trace Ru was not shown in the XRD. Further ICP-OES analysis revealed that the mass fraction of ruthenium in the trace ruthenium-modified cobalt tetroxide nanocage catalysts prepared in each embodiment was within the range of 0.22-0.56 wt%. For example, in the trace ruthenium-modified cobalt tetroxide nanocage catalyst prepared in Example 1, the mass fraction of ruthenium in the catalyst was ~0.41 wt%; in the trace ruthenium-modified cobalt tetroxide nanocage catalyst prepared in Example 2, the mass fraction of ruthenium in the catalyst was ~0.22 wt%; and in the trace ruthenium-modified cobalt tetroxide nanocage catalyst prepared in Example 3, the mass fraction of ruthenium in the catalyst was ~0.56 wt%.

[0076] The trace ruthenium-modified cobalt tetroxide nanocage catalysts prepared in each example were applied to the electrocatalytic oxidation of ethylene to 2-bromoethanol, all showing excellent Faradaic efficiency. Example 1 below uses the trace ruthenium-modified cobalt tetroxide nanocage catalyst prepared in Example 1 in the electrocatalytic oxidation of ethylene to 2-bromoethanol at a concentration of 0.5 mg cm⁻¹. -2 Regarding specific applications, the catalysts prepared in other examples were used in the electrocatalytic oxidation of ethylene to prepare 2-bromoethanol at a concentration of 0.25-1.0 mg / cm³. -2 At the catalyst loading levels, the trace ruthenium-modified cobalt tetroxide nanocage catalysts of each embodiment all showed application effects comparable to those in Application Example 1 below.

[0077] Application Example 1

[0078] The application of the trace ruthenium-modified cobalt tetroxide nanocage catalyst prepared in Example 1 as an anode material for the electrocatalytic oxidation of ethylene to 2-bromoethanol, and related test methods and results.

[0079] Step 1: Weigh 10 mg of the catalyst prepared in Example 1 using an analytical balance, and simultaneously take 100 μL of isopropanol and 20 μL of 0.5 wt.% Nafion solution. Mix the three together and place them in a sample vial for sonication for 2 hours.

[0080] Step 2: Cut out a 1×3cm piece2 Take a piece of carbon paper, wrap non-conductive tape around the center, leaving a 1×1cm section. 2 For space-drop coating of catalyst, a measured amount of the catalyst solution prepared in step one is added dropwise to a 1×1 cm² column. 2 On the carbon paper in the region, the catalyst loading was 0.5 mg cm⁻¹ -2 It is dried at room temperature or under infrared light and used as a working electrode.

[0081] Step 3: Using Ag / AgCl as the reference electrode and a platinum sheet as the counter electrode, a three-electrode system was formed together with the working electrode and placed in an H-type electrolytic cell. 0.1M potassium bromide was used as the electrolyte solution, and tests were conducted at different potentials. The yields of the product 2-bromoethanol and the byproduct ethylene glycol were analyzed by proton nuclear magnetic resonance spectroscopy.

[0082] The application effects of the trace ruthenium-modified cobalt tetroxide nanocage catalyst prepared in Example 1 are as follows: Figures 4-6 .in Figure 4 The figure shows the electrochemical polarization curves of the catalysts prepared in Example 1 (labeled "Example"), Comparative Examples 1 and 2 in a three-electrode reaction cell and 0.1 M potassium bromide electrolyte. The figure shows the current density of the trace ruthenium-modified cobalt tetroxide nanocage catalyst prepared in Example 1 at different potentials. At the same potential, this catalyst exhibits the highest current density and the lowest overpotential, reaching a current density of 10 mA cm⁻¹. -2 When the overpotential was reduced by 106 mV and 34 mV compared with Comparative Example 1 and Comparative Example 2, respectively, it demonstrated good conductivity and catalytic potential. Figure 5 The figure shows the Tafel slope diagrams of the catalysts prepared in Example 1 (labeled "Example") and Comparative Examples 1 and 2 in a three-electrode reaction cell and 0.1 M potassium bromide electrolyte. Figure 5 It can be seen that the catalyst in Example 1 has the smallest Tafel slope, at 55.9 mV dec. -1 , lower than Comparative Example 1 (104.4mV dec) -1 ) and Comparative Example 2 (66.3mV dec -1 This indicates that its reaction kinetics are the fastest and its catalytic activity is the highest. Figure 6 The figure shows the 2-bromoethanol Faraday efficiency of the catalysts prepared in Example 1 (labeled "Example"), Comparative Examples 1 and 2 in a three-electrode reaction cell and 0.1 M potassium bromide electrolyte. Figure 6It can be seen that the 2-bromoethanol Faradaic efficiency of the catalyst at 1.4V vs. RHE is significantly higher than that of Comparative Example 1, increasing from 84.4% to 93.9%. Compared with the ruthenium oxide nanoparticle catalyst with a high noble metal loading in Comparative Example 2, the 2-bromoethanol Faradaic efficiency in Comparative Example 2 is only 80.0%, and the 93.9% Faradaic efficiency of Example 1 also shows a significant advantage.

[0083] Comparative Example 1

[0084] This comparative example prepared a cobalt-based catalyst without noble metal modification, namely a pure cobalt tetroxide nanocage catalyst. The preparation steps of this cobalt tetroxide nanocage catalyst are as follows:

[0085] Step 1: Weigh 0.873g of cobalt nitrate hexahydrate and 0.984g of dimethylimidazole on an electronic balance, i.e., the molar ratio of cobalt nitrate to dimethylimidazole is 1:4. Dissolve them completely in 30ml and 10ml of methanol respectively under magnetic stirring.

[0086] Step 2: Slowly add the prepared dimethylimidazole methanol solution dropwise to the cobalt nitrate hexahydrate methanol solution, and react fully for 24 hours under magnetic stirring at 600 rpm to obtain a turbid purple solution product.

[0087] Step 3: Wash the product from Step 2 with methanol and anhydrous ethanol, filter it, dry it in a vacuum oven at 60°C for 12 hours, and then grind it to obtain product ZIF67.

[0088] Step 4: The product ZIF67 from Step 3 was calcined in a muffle furnace at 300°C for 2 hours to finally obtain the cobalt tetroxide nanocage catalyst of this comparative example.

[0089] The cobalt tetroxide nanocage catalyst prepared in Comparative Example 1 was applied to the electrocatalytic oxidation of ethylene to 2-bromoethanol. This cobalt-based catalyst served as the anode material for the electrocatalytic oxidation of ethylene to 2-bromoethanol. Except for the anode material, the method steps and parameters were consistent with those in Application Example 1. Tests showed that... Figure 4 Compared to the trace ruthenium-modified cobalt tetroxide nanocage catalyst of Example 1, the cobalt-based catalyst of Comparative Example 1 exhibited lower current densities in the test range, and significantly lower conductivity and catalytic potential. Figure 5 Compared to the trace ruthenium-modified cobalt tetroxide nanocage catalyst of Example 1, the cobalt-based catalyst of Comparative Example 1 exhibits a larger Tafel slope, indicating slower reaction kinetics. Figure 6The test results showed that using the cobalt-based catalyst of Comparative Example 1 as the anode material, the Faradaic efficiency of the electrocatalytic oxidation of ethylene to 2-bromoethanol was significantly lower than that of Example 1. At 1.4V vs. RHE, the Faradaic efficiencies of 2-bromoethanol in Comparative Example 1 and Example 1 were 84.4% and 93.9%, respectively.

[0090] Comparative Example 2

[0091] Commercially available ruthenium oxide nanoparticles were used as Comparative Example 2 in the electrocatalytic oxidation of ethylene to 2-bromoethanol. Ruthenium oxide was used as the anode material in the electrocatalytic oxidation of ethylene to 2-bromoethanol. Except for the anode material, the method steps and parameters were the same as in Application Example 1. Tests showed that... Figure 4 Compared to the trace ruthenium-modified cobalt tetroxide nanocage catalyst of Example 1, the commercial ruthenium oxide catalyst of Comparative Example 2 exhibited lower current densities in the test range throughout the testing period, and significantly lower conductivity and catalytic potential. Figure 5 The test results show that its reaction kinetics are also relatively slow. For example... Figure 6 The test results showed that using the commercial ruthenium oxide catalyst of Comparative Example 2 as the anode material, the Faradaic efficiency for the electrocatalytic oxidation of ethylene to 2-bromoethanol was approximately 80.0%, which was significantly lower than that of Example 1. This indicates that the trace ruthenium-modified cobalt tetroxide nanocage catalyst of Example 1 can combine cost and performance advantages.

[0092] It should be noted that the specific implementation methods described above provide a detailed explanation of the technical solution and application results of the present invention. Readers should understand that the above embodiments are only the most preferred embodiments and are not intended to limit the present invention. Modifications or equivalent substitutions made by those skilled in the art within the core theoretical scope of the present invention should all fall within the protection scope of the present invention.

Claims

1. The application of a trace ruthenium-modified cobalt-based nanocage catalyst, characterized in that: The catalyst is used in the electrocatalytic preparation of 2-bromoethanol from ethylene; the application is as follows: the trace ruthenium-modified cobalt tetroxide nanocage catalyst is attached to carbon paper as a working electrode, and potassium bromide solution is used as the electrolyte; The trace ruthenium-modified cobalt-based nanocage catalyst was prepared by ion adsorption, comprising the following steps: 1) Cobalt nitrate hexahydrate and dimethylimidazole were added to methanol and stirred continuously until completely dissolved to obtain methanol solutions of cobalt nitrate hexahydrate and dimethylimidazole, respectively. 2) The above dimethylimidazole methanol solution was added dropwise to the cobalt nitrate hexahydrate methanol solution and stirred at room temperature to obtain a turbid purple solution. 3) The product obtained in step 2) was washed sequentially with methanol and anhydrous ethanol, filtered, dried in a vacuum oven, and ground to obtain the precursor ZIF67. 4) Add the precursor ZIF67 and ruthenium chloride to ethanol respectively, and stir continuously until they are evenly dispersed to obtain ethanol solutions of ruthenium chloride and ZIF67. 5) Add the ruthenium chloride ethanol solution dropwise to the ethanol solution containing ZIF67, stir thoroughly to allow the ruthenium ions in the solution to be fully adsorbed on the surface of ZIF67, then wash with anhydrous ethanol, filter, dry in a vacuum oven, grind to obtain trace ruthenium modified ZIF67. 6) The ruthenium-modified ZIF67 is calcined in a muffle furnace to obtain the trace ruthenium-modified cobalt tetroxide nanocage catalyst.

2. The application of the trace ruthenium-modified cobalt-based nanocage catalyst according to claim 1, characterized in that: The trace ruthenium-modified cobalt-based nanocage catalyst is a trace ruthenium-modified cobalt tetroxide nanocage catalyst. The trace ruthenium-modified cobalt tetroxide nanocage catalyst is composed of two components: cobalt tetroxide and trace amounts of ruthenium oxide. The microstructure of the trace ruthenium-modified cobalt tetroxide nanocage catalyst is as follows: several cobalt tetroxide nanoparticles form a framework and are enclosed to form several hollow polyhedra, namely the cobalt tetroxide nanocages, and several ruthenium oxide nanoparticles are dispersed and adsorbed on the surface of the cobalt tetroxide nanocages.

3. The application of the trace ruthenium-modified cobalt-based nanocage catalyst according to claim 2, characterized in that: The ruthenium loading of the catalyst is 0.22-0.56 wt%, where ruthenium loading refers to the mass percentage of ruthenium in the catalyst.

4. The application of the trace ruthenium-modified cobalt-based nanocage catalyst according to claim 1, characterized in that: In step 1), the amount of cobalt nitrate hexahydrate and dimethylimidazole added satisfies a molar ratio of 1:2 to 1:

4.

5. The application of the trace ruthenium-modified cobalt-based nanocage catalyst according to claim 1, characterized in that: The total volume of methanol used in the methanol solution of cobalt nitrate hexahydrate and the methanol solution of dimethylimidazole formed in step 1) satisfies the following ratio: 40~120 mL : 3~9 mmol relative to the molar amount of cobalt nitrate hexahydrate added in step 1).

6. The application of the trace ruthenium-modified cobalt-based nanocage catalyst according to claim 1, characterized in that: In step 4), the mass of ruthenium chloride added is 4 to 16 wt% of the mass of ZIF67 added.

7. The application of the trace ruthenium-modified cobalt-based nanocage catalyst according to claim 1, characterized in that: In step 6), in order to ensure that the catalyst precursor is fully oxidized, it is calcined in a muffle furnace at a temperature of 300-400 °C for 1-2 hours.

8. The application of the trace ruthenium-modified cobalt-based nanocage catalyst according to claim 1, characterized in that: Using Ag / AgCl as the reference electrode and a platinum sheet as the counter electrode, a three-electrode system was formed to carry out the electrocatalytic reaction of ethylene to 2-bromoethanol in an H-type electrolytic cell.

9. The application of the trace ruthenium-modified cobalt-based nanocage catalyst according to claim 1, characterized in that: The trace ruthenium-modified cobalt tetroxide nanocage catalyst was loaded onto carbon paper at a loading of 0.25-1.0 mg / cm³. -2 .

Citation Information

Patent Citations

  • Pt monatomic and nano-particle coexisting catalyst, preparation method and application of Pt monatomic and nano-particle coexisting catalyst

    CN118976514A